Association between changes in heart rate variability during the anticipation of a stressful situation and the stress-induced cortisol response. (August 2018) - Pulopulos, Matias M.; Vanderhasselt, Marie-Anne; De Raedt, Rudi
Highlights: Heart rate variability and cortisol levels were measured in 171 healthy adults before, during, and after a stressful task. Changes in heart rate variability due to the anticipation of the stress task were related to the stress-induced cortisol increase. Changes in heart rate variability due to the stress task were not related to the stress-induced cortisol increase. Abstract: Vagal activity – reflecting the activation of stress regulatory mechanisms and prefrontal cortex activation – is thought to play an inhibitory role in the regulation of the hypothalamus–pituitary–adrenal axis. However, most studies investigating the association between stress-induced changes in heart rate variability (HRV, an index of cardiac vagal tone) and cortisol have shown a non-significant relationship. It has been proposed that physiological changes observed during anticipation of a stressor allow individuals to make behavioral, cognitive, and physiological adjustments that are necessary to deal with the upcoming actual stressor. In this study, in a large sample of 171 healthy adults (96 men and 75 women; mean age = 29.98, SD = 11.07), we investigated whether the cortisol response to a laboratory-based stress task was related to anticipation-induced or stress task-induced changes in HRV. As expected, regression analyses showed that a larger decrease in HRV during the anticipation of a stress task was related to higher stress task-induced cortisol increase, but not cortisol recovery. In line with prior research, the stress task-induced change in HRV was not significantly related to cortisol increase or recovery. Our results show for the first time that anticipatory HRV (reflecting differences in stress regulation and prefrontal activity before the encounter with the stressor) is important to understand the stress-induced cortisol increase.